(untitled) (Physical Education, Health and Social Sciences, 2026)
This research focused on formulation of combined coating from olive leaves extract, sunflower oil on the life span of guava fruits during storage. The treatments were as follows: To (control), T1 (2% olive leaves extract and1% sunflower oil ), T2 (4% olive leave extract and 2% sunflower oil), T3 (6% olive leaves extract and 3% sunflower oil), T4 (8% olive leaves extract and 4% sunflower oil), T5 (10% olive leaves extract and 5% sunflower oil), T6 (12% olive leaves extract and 6% sunflower oil) and T7 (14% olive leaves extract and 7% sunflower oil)Physicochemical and organoleptic properties were assessed at seven-day intervals over a period of 28 days. Decline was observed in firmness, moisture content, weight loss, acidity, vitamin C levels, appearance, flavor, texture, and overall acceptability. While pH and TSS increased significantly. There was a notable (p<0.05) rise in pH from 4.12 to 5.29 and TSS from 7.63 to 10.72 ̊ brix. The titrable acidity, on the other hand, reduced significantly (p<0.05) from 0.69 to 0.47, the vitamin C content from 180.11 to 165.41 mg/100g, and the moisture content. (from 85.96 to 74.18), firmness (from 7.40 to 3.34),weight loss (from 5.17 to 10.86), reducing sugar (from 4.39 to 5.25), non-reducing (from 3.11 to 3.62), flavor (from 8.11 to 4.41), appearance (from 8.05 to 2.40) and overall acceptability (from 8.18 to 4.44).Sunflower oil and olive leaf extract synergistically enhance fruit coatings by forming a protective film, providing antioxidant and antimicrobial properties, and acting as a moisture barrier to preserve shelf life while retaining quality. While the physicochemical and sensory analysis, T7 (14% olive leaves extract and 7%), followed by T6 (12% olive leaves extract and 6%Sunflower oil), was found best than other treatments, demonstrating superior quality and stability throughout storage.